Not so sustainable? Images of bioeconomy by future environmental professionals and citizens. (10th February 2019) - Vainio, Annukka; Ovaska, Ulla; Varho, Vilja
Abstract: This two-part study explored future environmental professionals' and citizens' views of bioeconomy and compared them to the official definitions. Essays written by future environmental professionals (N = 47) were analysed using thematic analysis. Four dimensions of the bioeconomy visions were identified: "drivers vs barriers", "change in technology vs lifestyles", "biological vs any sustainable resources" and "change as sustainable vs risky". The quantitative survey of Finnish citizens (N = 1020) was analysed with exploratory factor analysis and linear regression. Five dimensions emerged: "bio-based resources", "social and economic sustainability", "environmental degradation", "non-material values" and "scientific and technological advancement". The majority of respondents imagined a moderate increase in the use of bio-based resources and the scientific and technological advancement. The majority imagined no change in the social and economic sustainability and non-material values. The respondents were divided rather equally into those who imagined environmental degradation to worsen, those who imagined it to improve, and those who imagined it to stay the same. These findings demonstrate that citizens and future environmental professionals are critical of the environmental sustainability of bioeconomy, and that they perceive lifestyle changes and non-material values as a part of bioeconomy, which are not currently captured by official bioeconomy policies. Highlights: The visions of respondents were broader than official visions. Change in lifestyle and values emerged as an alternative to technological change. Bioeconomy was viewed as based on biological resources or any sustainable resources. Technological advancement and use of bio-based resources were expected to increase. Respondents were critical about the sustainability of bioeconomy.